The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.heliyon.2020.e04229
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a temporal lobe cavernous angioma to control epileptic seizures in a patient with tuberous sclerosis complex

Abstract: A patient with tuberous sclerosis complex (TSC) and a left temporal cavernous angioma (CA) presented with treatment-resistant epilepsy. We evaluated the patient to determine the best treatment option. Patient and methods: A 7-year-old boy with TSC exhibited weekly impaired awareness seizures and was diagnosed with TSC based on the modified Gomez's criteria. The presence of cortical tubers had been noted by his physicians. However, left temporal CA had not been diagnosed. He was referred to our facility for fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
(11 reference statements)
0
2
0
Order By: Relevance
“…Sakakura et al. 10 reported a 33 years old man diagnosed with TSC since he exhibited weekly impaired awareness seizures when he was 7 years old. He reached seizure‐free for 10 years after the removal of the cavernous angioma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sakakura et al. 10 reported a 33 years old man diagnosed with TSC since he exhibited weekly impaired awareness seizures when he was 7 years old. He reached seizure‐free for 10 years after the removal of the cavernous angioma.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, there are few reports that patients are free from TSC-related intractable epilepsy when TSC and other brain lesions are concomitant. Sakakura et al 10 reported a 33 years old man diagnosed with TSC since he exhibited weekly impaired awareness seizures when he was 7 years old. He reached seizure-free for 10 years after the removal of the cavernous angioma.…”
Section: Introductionmentioning
confidence: 99%